Effect of steroids on inflammatory markers and clinical parameters in congenital open heart surgery: a randomised controlled trial. (28th April 2015) - Amanullah, Muhammad M.; Hamid, Mohammad; Hanif, Hashim M.; Muzaffar, Marium; Siddiqui, Maria T.; Adhi, Fatima; Ahmad, Khabir; Khan, Shahjahan; Hasan, Zahra
Abstract: Background: Cardiopulmonary bypass is associated with systemic inflammatory response. Steroids suppress this response, although the therapeutic evidence remains controversial. We hypothesised that intravenous steroids in children undergoing open-heart surgery would decrease inflammation leading to better early post-operative outcomes. We conducted a randomised controlled trial to evaluate the trends in the levels of immunomodulators and their effects on clinical parameters. Objective: To assess the effects of intravenous steroids on early post-operative inflammatory markers and clinical parameters in children undergoing open-heart surgery. Materials and methods: A randomised controlled trial involving 152 patients, from one month up to 18 years of age, who underwent open-heart surgery for congenital heart disease from April 2010–2012 was carried out. Patients were randomised and administered either three scheduled intravenous pulse doses of dexamethasone (1 mg/kg) or placebo. Blood samples were drawn at four time intervals and serum levels of inflammatory cytokines – Interleukin-6, 8, 10, 18, and tumour necrosis factor-alpha – were measured. Clinical parameters were also assessed. Results: Blood cytokine levels were compared between the dexamethasone (n=65) and placebo (n=64) groups. Interleukin-6 levels were lower at 6 and 24 hours post-operatively (p<0.001), and Interleukin-10 levels were higher 6 hours post-operatively (p<0.001) in the steroid group. Interleukin-8, 18, and tumour necrosis factor-alpha levels did not differ between the groups at any time intervals. The clinical parameters were similar in both the groups. Conclusion: Dexamethasone caused quantitative suppression of Interleukin-6 and increased Interleukin-10 activation, contributing to reduced immunopathology, but it did not translate into clinical benefit in the short term.